The Disappearance of the Human Y - Chromosome: Exploring the Impact of Genetic Drift and Mutation on Human Evolution - Manchana, Ramakrishna (Journal of Research in Science and Engineering, 2025)
Sex determination in humans is primarily controlled by sex chromosomes, with males possessing an XY chromosome pair and females an XX pair. The Y chromosome, which plays a crucial role in initiating male development, has been undergoing progressive degeneration for millions of years. Over time, the Y chromosome has lost most of its genes, leading to speculation about its eventual disappearance. If this trend continues, alternative mechanisms, such as autosomal genes, may take over male - determining functions, as seen in some species. Evolutionary forces such as genetic drift, mutation and lack of recombination have contributed to the Y chromosome's decline. However, recent studies indicate that the Y chromosome has developed mechanisms to slow down its degeneration, potentially ensuring its survival. If the Y chromosome eventually disappears, human evolution may witness a shift in sex determination pathways, potentially leading to speciation.